Photoevaporation and Close Encounters: How the Environment around Cygnus OB2 Affects the Evolution of Protoplanetary Disks - Guarcello, M. G. (2023)
In our Galaxy, star formation occurs in a variety of environments, with a large fraction of stars formed in clusters hosting massive stars. OB stars have important feedback on the evolution of protoplanetary disks orbiting around nearby young stars and likely on the process of planet formation occurring in them. The nearby massive association Cyg OB2 is an outstanding laboratory to study this feedback. It is the closest massive association to our Sun and hosts hundreds of massive stars and thousands of low-mass members, both with and without disks. In this paper, we analyze the spatial variation of the disk fraction (i.e., the fraction of cluster members bearing a disk) in Cyg OB2 and study its correlation with the local values of far-ultraviolet (FUV) and extreme-ultraviolet (EUV) radiation ﬁelds and the local stellar surface density. We present deﬁnitive evidence that disks are more rapidly dissipated in the regions of the association characterized by intense local UV ﬁelds and large stellar density. In particular, the FUV radiation dominates disk dissipation timescales in the proximity (i.e., within 0.5 pc) of the O stars. In the rest of the association, EUV photons potentially induce a signiﬁcant mass loss from the irradiated disks across the entire association, but the efﬁciency of this process is reduced at increasing distances from the massivestars owing to absorption by the intervening intracluster material. We ﬁnd that disk dissipation due to close stellar encounters is negligible in Cyg OB2 and likely to have affected 1% or fewer of the stellar population. Disk dissipation is instead dominated by photoevaporation. We also compare our results to what has been found in other young clusters with different massive populations, concluding that massive associations like Cyg OB2 are potentially hostile to protoplanetary disks but that the environments where disks can safely evolve in planetary systems are likely quite common in our Galaxy.